2022
DOI: 10.1371/journal.pone.0272269
|View full text |Cite
|
Sign up to set email alerts
|

Automatic grading for Arabic short answer questions using optimized deep learning model

Abstract: Auto-grading of short answer questions is considered a challenging problem in the processing of natural language. It requires a system to comprehend the free text answers to automatically assign a grade for a student answer compared to one or more model answers. This paper suggests an optimized deep learning model for grading short-answer questions automatically by using various sizes of datasets collected in the Science subject for students in seventh grade in Egypt. The proposed system is a hybrid approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The results demonstrated that the system using bidirectional encoder representations from transformer model and fine-tuning methods could enhance the accuracy of shortanswer grading [15]. Abdul Salam et al (2022) proposed a hybrid approach that combined long short-term memory (LSTM) networks and grey wolf optimizer to automatically grade short-answer questions. Simulation results indicated better performance of this hybrid model, although the training time was longer [16].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated that the system using bidirectional encoder representations from transformer model and fine-tuning methods could enhance the accuracy of shortanswer grading [15]. Abdul Salam et al (2022) proposed a hybrid approach that combined long short-term memory (LSTM) networks and grey wolf optimizer to automatically grade short-answer questions. Simulation results indicated better performance of this hybrid model, although the training time was longer [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abdul Salam et al (2022) proposed a hybrid approach that combined long short-term memory (LSTM) networks and grey wolf optimizer to automatically grade short-answer questions. Simulation results indicated better performance of this hybrid model, although the training time was longer [16]. Filighera et al (2023) designed a blackbox adversarial attack specifically for educational shortanswer grading scenarios to study the robustness of grading models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The model was applied on dataset with 330 student's answers. It achieved 0.81 value as a Root Mean Square Error (RMSE) and 0.94 value as a Pearson correlation r. In [15], the authors proposed an automatic grading for Arabic short answer questions using optimized deep learning model. They used a hybrid LSTM and GWO model to predict the short answer grade questions for the students in science.…”
Section: Related Workmentioning
confidence: 99%
“…Matching Python, YOLO PMFU [12] 2019. Matching Python, MATLAB, CNN FCAI-BU [13] 2022. Short answer Python, LSTM with GWO ITD-AATSU [14] 2021.…”
Section: Related Workmentioning
confidence: 99%
“…The chosen systems satisfying the previously given criteria were developed at the School of Electrical Engineering, University of Belgrade (SEE-UB) [8], School of Engineering, Edith Cowan University (SE-ECU) [9], Department of Telematic Engineering, University Carlos III of Madrid (DTE-UCM) [10], School of Electronic and Information Engineering, Foshan University (SEIE-FU) [11], Prince Mohammad bin Fahd University (PMFU) [12], Artificial intelligence Department, Faculty of Computers and Artificial Intelligence, Benha University (FCAI-BU) [13], Information Technologies Division, Adana Alparslan Turkes Science and Technology University (ITD-AATSU) [14], School of Software South China, University of Technology Guangzhou and College of Medical Information Engineering, Guangzhou University of Chinese Medicine (SSSC-UTG/CMIE-GUCM) [15].…”
mentioning
confidence: 99%